PERKEMBANGAN INDUSTRI KERAJINAN KULIT DAN PENGARUHNYA TERHADAP KEHIDUPAN SOSIAL EKONOMI KELURAHAN SELOSARI KECAMATAN MAGETAN KABUPATEN MAGETAN - Limostin, Tea; Limostin, Tea (Candi, 2013)
The objectives of research were to find out: (1) the development of leather craft industry in Selosari, (2) the role of local government in the development of leather craft industry in Selosari, and (3) the influence of leather craft industry on the society?s social economic life in Selosari. The methodology of this research was qualitative research. On this research used a single fixed case study which the object would be observed has limited and centralized on certain location which has specific characteristics. Considering the result of research, it could be concluded: (1) the development of leather craft production in Kelurahan Selosari has been beginning since 1960. In 1991 the leather craft center was officially established in Sawo Street. The number of its business unit was 36 SMEs with 223 workers and 11 joint ventures for the lower-middle craftsmen, (2) the Local Government played its part well in developing the leather craft business in Magetan, particularly Selosari. The roles it played were educational and facilitating ones to the craftsmen. Educational role included building, training, and information giving through guiding and counseling. Facilitating role included giving capital, technology, or equipment helps, and (3) the existence of leather craft in Selosari affected  the social economic life of Selosari people. The social effect included to improve the relationship between the members of society and to change the people?s social status from unemployed to craftsmen. The economic effect included to improve the income and wellbeing of Selosari people. Keyword : SMEs, leather craft, development, social effect, economy effect.